2005
DOI: 10.1097/01.ju.0000146683.31101.ff
|View full text |Cite
|
Sign up to set email alerts
|

On the Art of Anastomotic Posterior Urethroplasty: A 27-Year Experience

Abstract: Of the operative details 3 constitute the gold triad that assures a successful outcome, namely complete excision of scarred tissues, fixation of healthy mucosa of the 2 urethral ends and creation of a tension-free anastomosis. When the bulboprostatic urethral gap is 2.5 cm or less, restoration of urethral continuity may be accomplished with a perineal procedure after liberal mobilization of the bulbar urethra. For defects of 2.5 cm or greater the elaborated perineal or perineo-abdominal transpubic procedure sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
89
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 15 publications
4
89
1
3
Order By: Relevance
“…A similar trend was evident in post traumatic strictures in the present study. Furthermore, the results were much better in Numerous studies support the occurrence of complications after urethral injury following a pelvic fracture, due to the injury itself rather than the surgical technique (14)(15)(16). We encountered complications in 26 patients with post traumatic strictures: infection, re-stenosis, impotence, urinary incontinence, urethracutaneous fistulae, wound dehiscence and ejaculatory disturbances, with rates acceptable in comparison to other studies (17,18).…”
Section: Discussionmentioning
confidence: 67%
“…A similar trend was evident in post traumatic strictures in the present study. Furthermore, the results were much better in Numerous studies support the occurrence of complications after urethral injury following a pelvic fracture, due to the injury itself rather than the surgical technique (14)(15)(16). We encountered complications in 26 patients with post traumatic strictures: infection, re-stenosis, impotence, urinary incontinence, urethracutaneous fistulae, wound dehiscence and ejaculatory disturbances, with rates acceptable in comparison to other studies (17,18).…”
Section: Discussionmentioning
confidence: 67%
“…In this procedure, the number of patients with impotence according to the IIEF-5 criteria was similar to the number of those without impotence. We did not expect any change in erectile function in those who underwent the end-to-end anastomosis, as Koraitim [13] suggest that impotence is usually related to the original trauma and rarely (2%) to urethroplasty itself. Furthermore, no patient reported a decline in erectile function after end-to-end anastomosis in a study by Barbagli et al [14].…”
Section: Discussionmentioning
confidence: 89%
“…However, in rate cases of female urethral distraction injury, some authors have suggested immediate open realignment to avoid subsequent urethravaginal fistulae or urethral stricture. 1 Endoscopc procedures, such as cutting a tunnel between the two ends of the avulsed urethra (cut-to the light procedure), can have unacceptable failure and complication rates, including coring of false passage that inadvertently bypasses the bladder neck. Pro-operative MRI, prior to perineal urethroplasty, is deemed necessary by some authors, since it can reveal the presence of associated corporal rupture, corporal body avulsion, and significant ischial fractures that may interfere with perineal repair.…”
Section: Discussionmentioning
confidence: 99%
“…Suprapubic drainage is maintained until associated injuries have healed and the patient can be places appropriately for the reconstructive procedure which my take from 3 to 12 months. 1 At three months, the resulting hematoma resolves and scar tissues at the injury site become stable (complete fibrosis) complete ambulation of the patient. At this stage, perianal urethroplasty comes into play, especially with long strictures.…”
mentioning
confidence: 99%
See 1 more Smart Citation